Cost-effectiveness of new oral anticoagulants in the treatment and secondary prevention of venous thromboembolism - A. V. Rudakova (Столичная издательская компания, 2015)
Aim. To assess the cost-effectiveness of apixaban in the treatment and secondary prevention of venous thromboembolism (VTE) compared with low molecular weight heparin (LMWH)/warfarin and other new oral anticoagulants (NOACs). Material and methods. Cost-effectiveness analysis was performed using a Markov model, developed on the basis of the results of AMPLIFY AMPLIFY-Ext trials, and network meta-analyzes on the use of antithrombotic drugs in acute VTE and long-term administration after VTE. Markov cycle duration was 3 months. The duration of therapy in the simulation was 6 and 12 months. The time horizon of the study was 5 years. Life expectancy and costs were discounted by 3.5% per year. The costs on drugs were estimated based on the registered marginal cost price. Besides, the analysis was performed to the weighted average auctions prices for NOACs. The costs of monitoring and treatment of complications were calculated on the basis of the collective agreement of compulsory health insurance system (St. Petersburg, 2015).  Results. Apixaban provided significant cost savings compared with other modes of anticoagulant therapy for hospital treatment. Apixaban provided cost savings compared with other NOACs with a minimal increase in life expectancy with regard to quality in long-term analysis. Apixaban provided an increase in life expectancy compared with the appointment of LMWH/warfarin, but required some increase in costs. At therapy duration of 6 months, the costs per one additional year of life with regard to quality and to one additional calendar year of life were 309.8-403.7 and 481.6-627.4 thousand rubles, respectively; at therapy duration of 12 months - 1254.4-1476.9 and 649.0-764.1 thousand rubles, respectively.  Conclusion. Apixaban provided a reduction in the incidence of bleeding compared with other NOACs and LMWH/warfarin with comparable efficacy in treatment and secondary prevention of VTE. Apixaban therapy costs were lower than these for other NOACs, and the additional cost of apixaban therapy compared with LMWH/warfarin proved to be highly cost effective in the treatment of 6 months duration and economically acceptable in therapy during 12 months.